THE WINDOW OF OPPORTUNITY: Memahami Aspek Penting Masa Perkembangan Anak Usia Dini - Hariyanto Hariyanto (LP2M Universitas Ibrahimy, 2014)
Window Of Opportunity is another term of the Golden Age that had been attached as an important period of the children, Window Of Opportunity is a period where the children learn the path of character, attitude, intellectual, emotional, and moral formed. The better the quality of parenting, it means more and good learning paths formed in his brain